Topiramate inhibits offensive aggression through targeting ventrolateral periaqueductal gray. (15th December 2020) - Chou, Dylan
Abstract: Topiramate is an approved antiepileptic drug clinically used to treat epilepsy and prevent migraines. Currently, topiramate has been found to be effective in treating aggressive symptoms in neuropsychiatric patients. In preclinical studies, however, the effects and mechanisms of topiramate on offensive aggression are still largely uninvestigated. Our previous studies indicated that glutamatergic transmission in the ventrolateral periaqueductal gray (vlPAG) plays a crucial role in regulating elements of offensive aggressive behaviors. In the present work, we investigated the actions of topiramate on vlPAG glutamatergic transmission and aggressive behaviors in group-housed (GH) and socially isolated (SI) rats. The results suggested that a single injection of topiramate systemically and dose-dependently inhibited elements of offensive aggressive behaviors of both GH and SI rats in the resident-intruder test (RIT), with long-lasting effective time profiles in SI rats. Moreover, systemic single administration of topiramate reduced the frequency and amplitude of miniature excitatory postsynaptic currents (mEPSCs) in the vlPAG. Bath perfusion of topiramate directly decreased the frequency and amplitude of mEPSCs and shortened the amplitude of evoked excitatory postsynaptic currents (EPSCs) in the vlPAG. Furthermore, intra-vlPAG single microinjection of topiramate dose-dependently inhibited offensive aggressive behaviors in GH and SI rats in a time-dependent manner. Additionally, both systemic and local topiramate inhibited offensive aggressive behaviors in a (2 R, 6 R )-hydroxynorketamine (HNK)-dependent rat model. In conclusion, the present results suggest that topiramate exerts anti-aggressive roles through its inhibitory actions on glutamatergic activities in the vlPAG. These preclinical results support topiramate as a candidate drug to treat patients with heightened offensive aggression. Highlights: Systemic topiramate reduces the behavioral elements of offensive aggression. Topiramate decreases glutamatergic activities in the vlPAG. Topiramate in the vlPAG inhibits offensive aggressive behaviors. Systemic and local topiramate attenuates offensive aggressive behaviors in a (2 R, 6 R )-HNK-dependent rat model.